(untitled) (Research, Society and Development, 2025)
Background: The Functional beauty is a new analytic technique which combines aesthetic treatment and functional maintenance of structures taking into account the myomodulation that occurs over time. This new approach seeks to improve perception and sensitivity so that it is possible to capture the essence of Beauty and expand the vision of facial harmony. Objective: Describe the fourth principles of the Functional Beauty technique and present the application of facial botulinum toxin based on it. Method: This publication brings a historical perspective of beauty and provides information on the specific characteristics of the technique and focuses on the fourth principles that guide facial assessments and the treatment panel. Results: Recommendations on injection techniques are provided for face based on the particular anatomy of each area, the focus is on the technique (fourth principles) and devices of injection of botulinum toxin. Marking photos are presented for illustration. Conclusion: Functional Beauty is an innovative aesthetic treatment technique, which aims not only at aesthetic benefits, but also at the absence of functional impairment in the short and long term not just treating defects and wrinkles.